(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Data about 5 species of corticioid fungi which are reported as new for Ukraine are provided. Among them Botryodasidium candicans J. Erikss. in anamorphous stage Haplotrichum capitatum (Link: Fr.) Willd., Bulbillomyces farinosus (Bres.) Jülich in anamorphous stage Aegerita candida Pers: Fr., Erythricium hypnophilum (P. Karst.) J. Erikss. et Hjortstam, Peniophora erikssonii Boidin and Tulasnella deliquescens (Juel) Juel. Description of specimens, drawings of their microstructures, information about substrats and locality, as well as data about substrate preferences and distribution of these species in the world is presented.